I capitoli di Isabella d’Aragona per gli ebrei di Bari - de Ceglia, Diego (Sefer yuḥasin ספר יוחסין | Review for the History of the Jews in South Italy | Rivista per la storia degli ebrei nell’Italia meridionale, 2020)
In questo lavoro si presenta l’edizione di un atto notarile relativo a un accordo stipulato tra l’Universitas di Bari e la locale comunità ebraica. L’atto contiene, tra gli inserti, un inedito privilegio concesso nel 1522 agli ebrei di Bari dalla feudataria della città Isabella d’Aragona e relativo alla sicurezza delle loro famiglie, dei loro beni e alle modalità di esercizio dell'attività di prestito. Dopo una attenta analisi del manoscritto, l’autore fornisce cenni biografici su Isabella d’Aragona e si sofferma ad analizzare gli articoli che compongono il privilegio, confrontandoli con provvedimenti simili già emessi in precedenza a favore degli ebrei del regno di Napoli. The privilege deed granted by Isabella of Aragon to the Jews of Bari This paper is the edition of a notarial deed relating to an agreement entered into between the universitas of Bari and the local Jewish community. Among other inserts, the deed contains an unpublished privilege granted in 1522 to the Jews of Bari by its feudal lord, Isabella of Aragon, concerning the safety of the Jewish families, their general assets, and the methods of exercising the activity of moneylending. The author provides a close analysis of the manuscript and a biographical note on Isabella of Aragon which explains the context in which the deed was granted, comparing its articles with similar measures previously issued in favour of Jews living in the Kingdom of Naples.